2000
DOI: 10.1177/104063870001200306
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Lesions Caused by a Strain ofChlamydia Suisin Weanling Pigs Infected at 21 Days of Age

Abstract: Abstract. The objective of this study was to determine whether a strain of Chlamydia suis shown previously to be an intestinal pathogen in gnotobiotic piglets could cause diarrhea and intestinal lesions in young weanling pigs. Pigs from 2 sows were randomly assigned to 2 groups. Group 1 included 13 pigs that were weaned at 24 hours of age and then housed in isolator units and fed milk replacer and unmedicated starter ration. Group 2 included 8 pigs that nursed their respective sows, consumed unmedicated starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…These positive data are small in number; however, among the microbial agents known to induce a lymphangitis, there are few that localize to the intestine and induce granulomatous obstruction of lymphatics [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These positive data are small in number; however, among the microbial agents known to induce a lymphangitis, there are few that localize to the intestine and induce granulomatous obstruction of lymphatics [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in which young pigs, calves, and nonhuman primates were inoculated with chlamydia have shown that the organisms cannot be demonstrated in the tissues after 12 weeks [5,18]. The chlamydia are known to persist in tissues in a form that cannot be readily demonstrated [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Chlamydia suis, which is a close relative of Chlamydia trachomatis, has been found in semen and genital tracts of boars, sows, bulls, and bucks; the clinical signs of the infected animals varied from conjunctivitis, to enteritis, to pneumonia. 14,25 Although there is no evidence about the possibility of infection in human beings with C. suis, the emergence of removable tetracyclineresistant plasmids in C. suis suggests a potential threat for the food safety of human beings. 34 Although Ch.…”
Section: Introductionmentioning
confidence: 99%